2018
DOI: 10.1080/14786419.2018.1519815
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of withaferin-A and withanolide-A in diploid (n = 12) and tetraploid cytotypes (n = 24) of “Rassbhary”, Physalis angulata L

Abstract: During the present study an analytical method based on reverse-phase high performance liquid chromatography photodiode array detection method was developed for simultaneous determination of withaferin-A and withanolide-A in plant parts of two cytotypes (diploid n=12 & tetraploid n=24) of Physalis angulata. All the plant parts were extracted in different solvent solutions i.e., acidic [HCl] methanol, methanol, n-hexane, chloroform. Both the compounds were comparatively analyzed. The results revealed that tetrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Tetraploid cytotypes of Physalis angutala Linn. from Rajasthan increased palmitic acid, linoleic acid and linolenic acid [61]. In the last century, many plant breeders have given objects based on the outstanding advantages of polyploids.…”
Section: Gigantic Effects and Enhance Phytochemicalmentioning
confidence: 99%
“…Tetraploid cytotypes of Physalis angutala Linn. from Rajasthan increased palmitic acid, linoleic acid and linolenic acid [61]. In the last century, many plant breeders have given objects based on the outstanding advantages of polyploids.…”
Section: Gigantic Effects and Enhance Phytochemicalmentioning
confidence: 99%
“…In many countries, such as China, Indonesia, Peru, Mexico, and Brazil, P. angulata is often used to treat a variety of illnesses, including dermatitis, tracheitis, impaludism, rheumatism, hepatitis, and analogous conditions [7][8][9][10]. Recently, increasing attention has been paid to the phytochemical and pharmacological aspects of P. angulata, and a variety of bioactive steroids with antitumor activities, including physagulins (A−Q), physangulidines (A−C), withangulatins (A−I), physalins (B, D, F−H), and withaminimin, have been isolated from the species [4,5,11]. Due to their important medicinal value, P. angulata plants have been widely cultivated in some regions of China for decades.…”
Section: Introductionmentioning
confidence: 99%
“…One major hindrance to the study of the pharmacokinetics of WFA has been the lack of appropriate analytical methods. In literature, there are a few HPLC and HPLC-ESI-MS/MS methods for the detection of have been published [125][126][127]. It has been reported that these methods could detect and quantify WFA in plasma up to a lower limit of 50 ng/mL.…”
Section: Pharmacokinetics Of a Single Intravenous Bolus Dose Of 10 Mgmentioning
confidence: 99%